Santri dan Politik: Revitalisasi Peran Santri dalam Mewujudkan Indonesia Emas 2045 - Dalailul Choir; Wahyu Trisno Aji (Pusat Riset dan Inovasi Nasional, 2024)
This paper aims to explain the importance of political literacy for Islamic boarding school students (santri) as a means to achieve Indonesia's golden age by 2045. This research focuses on qualitative methods with a literature study approach, focusing on primary data in the form of documentation, including books, journals, articles, and other literature related to political discussions and Islamic boarding school students. The results show that